Implementation of Lean Healthcare for Reducing National Health Insurance Out Patient’s Waiting Time using Value Stream Mapping Method - Nihayatul Muna, S.KM., MPH; Muhamad Ganda Saputra; Faizatul Ummah; Nahardian Vica Rahmawati; Ari Kusdiyana; Nuriyati Nuriyati (Jurnal Manajemen Kesehatan Indonesia, 2023)
Waiting time is one of quality standard in health services. The waiting time for national health insurance outpatients in Sosodoro Djatikoesoemo Hospital in Bojonegoro obtained an average monthly achievement of around 59.79% less than the standard from ministry of health’s regulation (80%). This study aimed to reduce patient waiting time using value stream mapping analysis and purpose the future stream mapping. This was a quantitative descriptive study using a cross-sectional design using Value Stream Mapping analysis. The sample was obtained by purposive sampling of 90 outpatients under national health insurance in Sosodoro Djatikoesoemo Hospital in Bojonegoro. The data was collected by using the observation table. The results found that two waste were found during outpatient flow including waiting and extra processing. In addition, the analysis obtained a Value Added Ratio (VAR) of 23.61% indicating that the service was not efficient compared with the provisions of Process Cycle Efficiency (> 30%). The future Stream Mapping was proposed and indicated a decrease in waiting time which was originally 99.21 minutes to 58.16 minutes. The possible improvement is the development of an electronic patient eligibility certificate of national health insurance where this improvement is useful in reducing patient waiting time by 41.05 minutes or around 41.37%. The management can consider to develop an electronic patient eligibility certificate in order to make the service delivery in out patient more efficient.